Traditional Chinese Medicine: A Class of Potentially Reliable Epigenetic Drugs - Zhu, Daoqi; Li, Aiwu; Lv, Ying; Fan, Qin (Frontiers in Pharmacology, 2022)
Epigenetics modification, especially DNA methylation plays a nonnegligible role in the occurrence and development of tumors. With the increasing studies indicated traditional Chinese medicine (TCM) plays a considerable role in anti-tumor by regulating the process of DNA methylation modification. Studies on TCM regulate DNA methylation modification are mostly focus on the whole genome and abnormal methylation status by active ingredients or single compounds and Chinese herb formula (CHF). The balance and overall concept of TCM theory coincides with the balance of DNA methylation modification in the tumor environment. Regardless how TCM modulates epigenetics in tumor shows that it is a class of potentially reliable epigenetic drug.